Micronutrient-deficient diets and possible environmental enteric dysfunction in Buruli ulcer endemic communities in Ghana: Lower dietary diversity and reduced serum zinc and vitamin C implicate micronutrient status a possible susceptibility factor. - Aloysius Dzigbordi Loglo; Philemon Boasiako Antwi; Kabiru Mohammed Abass; Samuel Osei-Mireku; George Amofa; Elizabeth Ofori; Jonathan Kofi Adjei; Michael Ntiamoah Oppong; Richard Odame Phillips; Reginald Annan; Barbara Engel; Rachel E Simmonds (PLoS Neglected Tropical Diseases)
Background The nutritional status of communities susceptible to Buruli ulcer (BU, a skin NTD caused by infection with Mycobacterium ulcerans) remains almost completely obscure. We have assessed the diets of BU patients vs. controls from the same BU-endemic communities, and compared their circulating biomarkers of nutrients and inflammation. Methods/principal findings We investigated two cohorts of BU patients and controls. The first were administered food frequency and multi-pass 24-hour recall questionnaires to determine patterns of foods consumed, nutrient intake and nutrient adequacy. The second used archived serum samples collected as baseline to measure the circulating concentration of zinc, vitamin C, CRP, IL-1β, IFN-γ, TNF-α and IL-6. Stunted growth was more prevalent than expected (31%), while 18% of participants were underweight and most had inadequate intake of all micronutrients except for carbohydrate. BU patients had a lower intake of, selenium, vitamin B12 and zinc, and for selenium and vitamin B12 a higher proportion had dietary insufficiency (40% vs. 15% and 80% vs. 55%, respectively). In line with this, BU patients had significantly lower levels of zinc in their serum, and more had levels below the normal range (72% vs. 43%). Despite many participants having a good intake of vitamin C, serum levels were low, and lower amongst the BU patients. As expected, there was little evidence of systemic inflammation (CRP <0.6 mg/L). Elevated IL-6 levels were present in several participants suggesting that environmental enteric dysfunction may be prevalent in these communities, however this was similar in cases vs. controls. Conclusions/significance Diet and nutritional status may be a contributing factor to BU pathogenesis. Protein and the micronutrients zinc, selenium, vitamin B12 and vitamin C may be of particular importance. Nutritional interventions may have potential for both prophylaxis and treatment of BU, which may be a cost-effective approach to achieving the NTD Roadmap goals.